Effects of Climate Change on the Eutrophication of Lakes and Estuaries - Karl Havens (EDIS)
Recent research suggests that climate change will reinforce the negative consequences of man-made eutrophication and make it more difficult to improve water quality in lakes and estuaries. This 3-page fact sheet was written by Karl Havens, and published by the UF Department of Sea Grant, September 2012.